Immobilized glucosyltransferase and sucrose synthase on Fe3O4@Uio-66 in cascade catalysis for the one-pot conversion of rebaudioside D from rebaudioside A. (July 2022) - Liu, Xiaojie; Hu, Yifan; Wei, Bin; Liu, Fang; Xu, Haichang; Liu, Changxia; Li, Ye; Liang, Hao
Abstract: Rebaudioside D (RD) is a natural low-calorie, high-sweet sweetener and an excellent sugar substitute. In this study, RD was produced by coupling glucosyltransferase (EUGT11) and sucrose synthase (SUS) with a novel strategy of immobilization to enhance the recyclability of enzymes and decrease the production costs of RD. Recombinant EUGT11 from Oryza sativa and SUS from Arabidopsis thaliana were expressed in Escherichia coli and immobilized onto Fe3 O4 @Uio-66 nanocomposite. The results of Fourier transform Infrared spectra (FT-IR), X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), magnetic susceptibility (VSM), thermogravimetric (TG) analysis and Brunauer–Emmett–Teller (BET) indicated that the magnetic nanocomposite Fe3 O4 @Uio-66 was successfully fabricated and the two enzymes were separately immobilized on Fe3 O4 @Uio-66. The reusability, storage, pH and temperature stabilities of the immobilized enzymes were investigated and compared to that of free enzymes. It was more stable towards temperature compared with free enzyme. The kinetic properties of immobilized EUGT11 showed a lower Vm and a higher Km compared to free EUGT11, and immobilized SUS showed a lower Vm and Km compared to free SUS. The immobilized SUS had around 56% residual activity upon storage a period of 10 days at 4 °C. After 8 times, the catalytic activity of immobilized double enzyme still retained around 80%, which showed a desirable stability and reduced the overall cost of enzymes, indicating that the immobilized enzymes had a good industrial application prospect in RD production. Graphical Abstract: ga1 Highlights: Double-enzyme biocatalyst of glucosyltransferase and sucrose synthase was prepared. Glucosyltransferase and sucrose synthase were first immobilized on Fe3 O4 @Uio-66. The thermostability of enzyme was improved by immobilization. The activity of immobilized double enzyme was maintained at 80% after 8 times of recycling.